2020
DOI: 10.1002/gps.5366
|View full text |Cite
|
Sign up to set email alerts
|

White matter lesions and temporal atrophy are associated with cognitive and neuropsychiatric symptoms in patients with hypertension and Alzheimer's disease

Abstract: An increasing evidence suggests hypertension (HTN) could be linked to cognitive impairment and incident Alzheimer's disease (AD). The precise mechanisms linking HTN and AD are not well-known. The aim of this study was to assess the putative association between HTN and AD. Methods: We assessed in patients with AD associations between HTN and demographic and clinical data, vascular risk factors, treatments, APOE genotypes, brain white matter hyperintensities (WMH), and medial temporal atrophy (MTA) in multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…PDC , encoding a phosphoprotein involved in the process of vision in the retina, has been associated with stress-induced hypertension [ 34 , 35 ]. Hypertension, in turn, has been associated with an increased risk to develop AD [ 36 , 37 ]. PTGS2 (prostaglandin-endoperoxide synthase 2) encodes the cyclooxygenase enzyme, involved in the biosynthesis of prostaglandins; different single nucleotide polymorphisms in PTGS2 have been associated with AD, resulting in protection or increased risk of developing the disease [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…PDC , encoding a phosphoprotein involved in the process of vision in the retina, has been associated with stress-induced hypertension [ 34 , 35 ]. Hypertension, in turn, has been associated with an increased risk to develop AD [ 36 , 37 ]. PTGS2 (prostaglandin-endoperoxide synthase 2) encodes the cyclooxygenase enzyme, involved in the biosynthesis of prostaglandins; different single nucleotide polymorphisms in PTGS2 have been associated with AD, resulting in protection or increased risk of developing the disease [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the enhanced postsynaptic activity promotes a more normal function of the cholinergic system [55,[61][62][63]. This is important in the medial temporal lobe and especially the hippocampus because both play a crucial role in memory [64,65]. On the other hand, the presence of vascular pathology causes arterial stiffness and modifies the structure of cerebral blood vessels and alters the delicate vasoregulatory mechanisms that ensure an adequate blood supply to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the temporal lobe was described in the early stages of neurodegenerative disorders. Temporal atrophy is associated with impaired cognitive function and neuropsychiatric symptoms in Alzheimer’s disease [ 31 , 32 ]. Recent studies suggested that Alzheimer’s disease degenerative pathologies contribute to white matter hyperintensity, in addition to cerebrovascular disease [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%